User Services and Data Management in the Luxembourg Income Study - John F. Coder (Luxembourg Income Study (LIS), 2000)
A major goal of the Luxembourg Income Study (LIS) has been to provide researchers with access to information about the social and economic characteristics of households and families for countries throughout the world. Since this information is in the form of data files containing actual observations from household surveys, the researcher does not need to rely on statistical summaries that others have previously created. They can create tabulations and statistical analyses from the survey data that precisely fit their needs and update them easily when new data become available. Further, a system to access these data has been developed which permits researchers to generate statistics from remote locations using email as a mechanism to transmit requests and forward results. Access to these data is, in fact, restricted to this system of remote access because much of the data available through the project has been provided by the member countries with the restriction that they not be redistributed or otherwise copied. The introduction describes the evolution of the techniques and methods used to maintain the databases of household microdata and to provide remote access services to users throughout the world. The discussion begins with an overview of the system. The final chapter presents results of a recent survey of LIS users.
Keywords: 330; Einkommensverteilung; Digitale Güter; Welt